A pre-monsoon precursor for foreshadowing of northeast monsoon rainfall over Tamilnadu - ASOKAN , R; BALACHANDRAN, S (MAUSAM, 2008)
A potential predictor for foreshadowing the Northeast Monsoon Rainfall over Tamilnadu (NEMRT) has been identified from the analysis of relationship between Surface Temperature Anomalies (STA) and NEMRT for the period 1901-2004. A Pre-monsoon Meridional Temperature Anomaly (PMTA) index is defined as the difference between the area averaged temperature anomalies over the regions (80° E - 90° E; 20° N - 25° N) and (80° E - 100° E; 5° S - 5° N) and this PMTA index is found to have significant inverse relationship with NEMRT. The Correlation Coefficient (CC) between PMTA index and NEMRT for the period 1901-2004 is -0.37 (significant at 95% level). The 30 year sliding correlation between PMTA index and NEMRT show significant CC with magnitude greater than 0.6 during the last two decades. The foreshadowing skill of PMTA index with reference to NEMRT is discussed by means of regression analysis and probability forecast methods.